2020
DOI: 10.7150/thno.47407
|View full text |Cite
|
Sign up to set email alerts
|

Screening for in-vivo regional contractile defaults to predict the delayed Doxorubicin Cardiotoxicity in Juvenile Rat

Abstract: Anthracyclines are key chemotherapeutic agents used in various adult and pediatric cancers, however, their clinical use is limited due to possible congestive heart failure (HF) caused by acute and irreversible cardiotoxicity. Currently, there is no method to predict the future development of the HF in these patients. In order to identify early biomarkers to predict anthracycline cardiotoxicity in long-term survivors of childhood cancer, this longitudinal study aimed to analyze early and late in-viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…Although the suppression of phosphorylation of cMyBP-C by this oxidation also requires more thorough investigation in cardiac disorders, there is evidence that the cross talk between cMyBP-C S-glutathionylation and PKA-dependent phosphorylation is an important determinant of altered cardiac function in stressful exercise in which the oxidation is increased and the phosphorylation is decreased ( Chakouri et al, 2018 ). A similar effect has been reported in doxorubicin-induced cardiac toxicity ( Chakouri et al, 2020 ).…”
Section: Integration Of Recent Advances In Structural States Of the Thin Filament As Controlled By Srx And Drx Thick Filament States Intesupporting
confidence: 84%
“…Although the suppression of phosphorylation of cMyBP-C by this oxidation also requires more thorough investigation in cardiac disorders, there is evidence that the cross talk between cMyBP-C S-glutathionylation and PKA-dependent phosphorylation is an important determinant of altered cardiac function in stressful exercise in which the oxidation is increased and the phosphorylation is decreased ( Chakouri et al, 2018 ). A similar effect has been reported in doxorubicin-induced cardiac toxicity ( Chakouri et al, 2020 ).…”
Section: Integration Of Recent Advances In Structural States Of the Thin Filament As Controlled By Srx And Drx Thick Filament States Intesupporting
confidence: 84%
“…Other short-term models use 2–3.4 mg/kg of DOX every other day, six times intraperitoneally (the total dose is 12–20 mg/kg) ( Zbinden et al, 1978 ; Lanza et al, 1989 ; Carvalho et al, 2010 ; Razmaraii et al, 2016 ; Cappetta et al, 2018 ; Aygun and Gul, 2019 ; Barış et al, 2019 ). Long-term rat models typically use 1–5 mg/kg every week for 2–12 weeks with a cumulative dose of 3–25 mg/kg ( Villani et al, 1991 ; Sacco et al, 2001 ; Sayed-Ahmed et al, 2001 ; Rahimi Balaei et al, 2010 ; Hydock et al, 2012 ; Hole et al, 2013 ; Toblli et al, 2014 ; Kang et al, 2017 ; Medeiros-Lima et al, 2019 ; Wang et al, 2019 ; Chakouri et al, 2020 ; Sharma et al, 2020 ). Thus, a short-term high-dose injection model would be suitable for assessing acute cardiotoxicity, while a long-term low-dose model would be suitable for assessing chronic cardiotoxicity.…”
Section: Anthracycline Cardiomyopathy Modelsmentioning
confidence: 99%
“…Consequently, the rates of severe cardiovascular complications have decreased recently [35]. However, juvenile DOX-induced cardiotoxicity is often characterized in preclinical models using high cumulative doses of DOX that are enough to cause immediate or delayed cardiac dysfunction [36][37][38][39]. We have previously shown that low doses of DOX administered to young mice did not cause immediate cardiac dysfunction but rather a latent (subclinical) cardiotoxicity which can be unmasked by exposure to adult-onset cardiovascular stressors such as high blood pressure [25] or psychosocial stress [40].…”
Section: Discussionmentioning
confidence: 99%